Respuesta :
-x^2 y^2 + x^4 + 4y^2 - 4x^2
= x^4 -x^2 y^2 - 4x^2 + 4y^2
= x^2 (x^2 - y^2) - 4 (x^2 - y^2)
= (x^2 - y^2)(x^2 - 4)
= (x + y)(x - y) (x + 2)(x - 2) (....using a^2 - b^2 = (a+b)(a-b) )
hope it helps
= x^4 -x^2 y^2 - 4x^2 + 4y^2
= x^2 (x^2 - y^2) - 4 (x^2 - y^2)
= (x^2 - y^2)(x^2 - 4)
= (x + y)(x - y) (x + 2)(x - 2) (....using a^2 - b^2 = (a+b)(a-b) )
hope it helps
Answer:
[tex](x + y)(x - y) (x + 2)(x - 2)[/tex]
Step-by-step explanation:
[tex]-x^2 y^2 + x^4 + 4y^2 - 4x^2[/tex]
Lets rearrange the terms
[tex]x^4 -x^2 y^2 - 4x^2 + 4y^2[/tex]
Then we group first two terms and last two terms
[tex](x^4 -x^2 y^2)+(- 4x^2 + 4y^2)[/tex]
Factor out each group
[tex]x^2(x^2 - y^2) - 4 (x^2 - y^2)[/tex]
[tex](x^2 - y^2)(x^2 - 4)[/tex]
Apply formula [tex]a^2 - b^2 = (a+b)(a-b)[/tex]
[tex](x + y)(x - y) (x + 2)(x - 2)[/tex]